2020
DOI: 10.1111/jth.15054
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of plasminogen activator inhibitor‐2 results in accelerated tumor growth

Abstract: Background: Upregulation of the plasminogen activation system, including urokinase plasminogen activator (uPA), has been observed in many malignancies, suggesting that co-opting the PA system is a common method by which tumor cells accomplish extracellular matrix proteolysis. PAI-2, a serine protease inhibitor, produced from the SERPINB2 gene, inhibits circulating and extracellular matrix-tethered uPA. Decreased SERPINB2 expression has been associated with increased tumor invasiveness and metastasis for severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…PAI-2 is a potent uPA inhibitor that exists in two forms: a 47 kDa nonglycosylated intracellular form and a secreted 60 kDa glycosylated form, but exists mainly in the prior form. The expression of the PAI-2 SERPINB2 gene is induced by inflammatory mediators such as TNF-α and lipopolysaccharides or by viral and bacterial infections [ 119 , 120 , 121 ]. It is expressed constitutively by various cell types like keratinocytes and syncytial trophoblasts and is also expressed as a result of inflammation or injury by various cell types, including monocytes, macrophages, EC, and fibroblasts, highlighting its important role in mediating wound healing and inflammation [ 122 ].…”
Section: Plasminogen Activator–plasmin Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…PAI-2 is a potent uPA inhibitor that exists in two forms: a 47 kDa nonglycosylated intracellular form and a secreted 60 kDa glycosylated form, but exists mainly in the prior form. The expression of the PAI-2 SERPINB2 gene is induced by inflammatory mediators such as TNF-α and lipopolysaccharides or by viral and bacterial infections [ 119 , 120 , 121 ]. It is expressed constitutively by various cell types like keratinocytes and syncytial trophoblasts and is also expressed as a result of inflammation or injury by various cell types, including monocytes, macrophages, EC, and fibroblasts, highlighting its important role in mediating wound healing and inflammation [ 122 ].…”
Section: Plasminogen Activator–plasmin Systemmentioning
confidence: 99%
“…PAI-2 levels are also elevated in trophoblasts emphasizing its vital role in embryogenesis; reduced plasma levels of PAI-2 in human embryos were associated with preeclampsia and intrauterine growth delay [ 121 ]. However, in vivo experiments on mice showed that mice deficient in PAI-2 exhibited normal development and survival [ 120 ]. Unlike PAI-1, elevated levels of PAI-2 in cancer are linked with reduced cancer progression and metastasis due to its inability to bind to vitronectin.…”
Section: Plasminogen Activator–plasmin Systemmentioning
confidence: 99%
“…Decreased PAI-2 expression has been associated with increased tumor invasiveness and metastasis for several types of cancer. In 50% of PAI-2-deficient mice aged over 18 months, spontaneous malignancies of vascular origin were found [19]. Moreover, accelerated tumor growth was observed in PAI-2-deficient mice when injected with B16 melanoma or Lewis lung carcinoma cells.…”
Section: Pai-2 and Senescencementioning
confidence: 99%
“…However, PAI-2 deficient mice had normal development, survival, fertility, and response to infections [143]. While no clear links with vascular disease have been documented, PAI-2 deficiency has shown an association with malignant tumour growth and metastasis by mechanisms that remain unclear [144].…”
Section: Effects Of Pai-2 Deficiencymentioning
confidence: 99%